Penerapan Metode C4.5 untuk Klasifikasi Mahasiswa Berpotensi Drop Out - Asmaul Husnah Nasrullah (ILKOM Jurnal Ilmiah, 2018)
The quality of education in universities can be seen from the high level of student success and the low failure of students. One indicator of student failure is the case of Drop Out (stop study). The problem of Drop Out becomes something interesting to study, because this can affect the quality of education. Faculty of Economics UNISAN Gorontalo is a favorite Faculty in UNISAN Gorontalo so it has a number of students of approximately 1000 students until 2017. But the ratio of the number of graduate students and not pass unbalanced. So as to produce the number of students Drop Out approximately 200 students per year. To solve the problem, we proposed a new model by utilizing a C4.5 computation method, in order to produce a pattern based on the results of the correct classification in determining the potential Drop Out students. The results obtained from the application of method C4.5 in this research is the discovery of 17 rules that can be used as a pattern to determine the potential students Drop Out.